Opaque or Transparent: Quality Disclosure Strategy for Accommodation-Sharing Platforms - Xin Fan; T.C.E. Cheng; Gang Li (Journal of Theoretical and Applied Electronic Commerce Research, 2022)
Compared with the conventional hotel providing a standardized service, individual supply on an accommodation-sharing platform makes consumers uncertain about service quality, which is mainly caused by information asymmetry between the consumers and individual hosts. In this paper, we develop a game-theoretic model to study the accommodation-sharing platform’s optimal quality information disclosure and its determining factors with consideration of consumer uncertainty. We find that it is optimal to provide either opaque, i.e., completely uninformative, or transparent, i.e., fully informative, quality information. We also examine the impacts of the incumbent hotel and market heterogeneity on the platform’s quality disclosure. The results show that market heterogeneity and the hotel’s service cost jointly affect the platform’s information disclosure strategy. In general, the sharing platform provides opaque information when market heterogeneity is relatively low but provides transparent information when market heterogeneity is relatively high. However, when market heterogeneity is medium, the hotel’s service cost plays a key role in affecting its pricing strategy, hence the information disclosure strategy of the platform. Specifically, a sufficiently high price of the hotel prompts the platform to disclose transparent information. These findings provide guidance for sharing platforms to design their information disclosure systems.